Pengaruh Kepemilikan Manajerial dan Profitabilitas Terhadap Nilai Perusahaan Dengan Kebijakan Hutang Sebagai Variabel Intervening - Prakoso, Riski Wisnu; Akhmadi, Akhmadi (Faculty of Economics and Business - Universitas Sultan Ageng Tirtaysa, 2020)
This paper discusses analyzing the significance of managerial ownership and profitability on firm value, analyzing the significance of the effect of profitability on firm value on the Indonesian Stock Exchange in 2015-208. The sample used in this study were 72 manufacturing companies listed on the Indonesia Stock Exchange in 2015-2018, consisting of several industrial sectors. The results of the research that tested the first hypothesis obtained that there was no influence of managerial ownership on firm value (rejected), the second hypothesis was obtained that there was a positive and significant effect of profitability on firm value in manufacturing companies (accepted), the third hypothesis obtained that there was no effect of debt policy on firm value ( rejected), the fourth hypothesis is obtained. There is no effect of managerial ownership on debt policy (rejected), the fifth hypothesis is obtained. There is a positive and significant effect. on profitability towards debt policy (rejected), the sixth hypothesis is obtained that there is no influence of managerial ownership on firm value with debt policy mediated (rejected) and the seventh hypothesis is obtained that there is an effect of profitability on firm value. by mediating debt policies in Manufacturing Companies in 2015-2015 (accepted).